Fresh Properties and Compressive Strength of 3D Printing Concrete Containing GGBS as Partial Cement Replacement - Juhari, Hajar Fathiah; Ali, Noorwirdawati; Abdullah, Siti Radziah; Salleh, Norhafizah; Abdul Hamid, Noor Azlina (Journal of Structural Monitoring and Built Environment, 2022)
3D printed concrete is a particular mix of concrete that has been specially prepared to flow easily through the printing nozzle. The foundations of 3D printed concrete constructions are stacked, with each layer put on top of a preceding layer of pumped concrete. Despite its potential, the construction industry has been confronted with several material issues. The cement replacement in the concrete has also been intensively studied, but in 3D printed concrete, this matter has not been seen clearly. It still cannot be seen whether the cement replacement produces a good result for the 3D printed concrete. This research investigated the fresh characteristics and compressive strength of 3D printed concrete using GGBS as a partial cement replacement in the mixture. In addition, the optimal proportion of GGBS as a partial cement replacement in 3D printed concrete is also evaluated. In this study, the fresh properties of 3D printing were examined by a flow table test, a buildability test, and an extrudability test, while compression strength was assessed for the mechanical properties. The percentage of GGBS used will vary from 20% to 50% with a 10% increment by weight of cement, and the water-cement ratio was fixed at 0.5. The cube specimen for the compression test was 50 mm x 50 mm x 50 mm and was cured for 7 and 28 days. The findings show that the flowability of this 3D printed concrete increased as the percentage of GGBS increased. All of the specimens also passed the buildability and extrudability tests. The compressive strength of this 3D printed also increased as the percentage increased, but it decreased back at 50% GGBS replacement. Overall, this experiment shows that 40% GGBS replacement is the optimum proportion as cement replacement in 3D printed concrete as it shows the highest compressive strength, which is 57.3 MPa.